Block Chain Technology and Financial Inclusion- A Systematic Review of Literature - Mohammed Abdulghani Taha (International Journal of Advanced Science and Technology, 2020)
The brainchild of Satoshi Nakamoto, Blockchain Technology, a concept on the rise which allows data to be shared but not copied is a phenomenal innovation made. Originally innovated for use in the digital currency, now a days it presents for applications in various industries and technologies. This Systematic Review aims to present a relation between the Blockchain Technology and how it could be used to lead to better Financial Inclusion. A Systematic Literature Review was conducted to identify the main objectives of the research and understand the various methodologies involved in researches on the topic. Major themes were also identified which included: A secure way of Financing, Legal Issues, Microfinance and Financial Inclusion. A total of 64 articles were shortlisted from a pool of 926 researches which were arrived at through major keyword searches. Furthermore Limitations to the study are also stated thereby providing a scope for further research with respect to major themes and suggestions for more empirical researches on the same.